Une guerre souterraine contre Louis XIV. L’Espagne, la Hollande et les projets de révolte de 1674 - Charles-Édouard Levillain (Mélanges de la Casa de Velázquez)
In 1674, as the guerre de Hollande (1672-1678) was raging, the Dutch Republic and the Spanish Crown backed several revolt projects in the kingdom of France that ultimately failed. These projects, which involved some 300 potential rebels, have long fascinated historians of early modern France, accustomed as they are to viewing the reign of Louis XIV as a time of forcible stabilization, following the numerous tax revolts which had beset the early 17th century. This article offers a fresh insight into the failed revolts of 1674 from a Spano-Dutch perspective, bringing in new sources and seeking to nuance an established consensus on the sturdiness of France’s maritimes defences. Although the conquest of Franche-Comté (1674) can rightly be described as a major strategic success for the French Crown, one should not underestimate the considerable anxiety caused by the fear of a Dutch amphibious attack on the French Atlantic coast. The story of this confrontation between France and the Spano-Dutch revolves around William III of Orange, who was in the process of becoming the linchpin of a broad transconfessional front against the Sun King.